Association of Obesity, Parity, and History of Knee Injury with Knee Osteoarthritis in Female - Triyadi, Ade; Pramudiyo, Riardi; Iwan A. R., Januarsih (Althea Medical Journal, 2015)
Background: Osteoarthritis is the most joint disorder among elderly. There are a lot of risk factors of knee osteoarthritis. Obesity and high frequent of parity can increase the load on knee joint. Knee injury also decreases the stability of knee joint on bearing body load. This study was conducted to observe the association of obesity, parity â¥3 times and history of knee injury with the occurrence of kneeÂ  osteoarthritis in female aged >50 years old.Methods: Case control design was chosen in this study. Female patients with age >50 years were recruited by consecutive sampling from rheumatology clinic at Dr. Hasan Sadikin General Hospital Bandung. Data were collected from August to September 2013. Minimal sample size was 60 samples calculated by rule of thumb formula. Obesity was measured by body mass index (BMI). Parity and history of knee injury were assessed by questionnaire. Those variables were analyzed by logistic regression method.Result: Obesity did not associate with knee osteoarthritis in this study, p=0.549 (odd ratio (OR) 1.32, 95% confidence interval (CI) 0.52â3.32). Parity was associated with knee osteoarthritis in this study p=0.001 (OR 4.7, 95% CI 1.89â11.68). History of knee injury was associated with knee osteoarthritis in this study, p=0.001 (OR 6.19, 95% CI 2.01â18.99).Conclusions: Parity â¥3 times and history of knee injury were associated with the occurrence of knee osteoarthritis. Obesity was not associated with the occurrence of knee osteoarthritis. [AMJ.2015;2(4):492â6]Â DOI:Â 10.15850/amj.v2n4.633